Analisis Persepsi Atas Kualitas, Ketersediaan, Harga Citra Merk Terhadap Kepuasaan Pelanggan Dan Kepercayaan Pelanggan Serta Dampaknya Pada Minat Beli Kembali Produk Obat Herbal XYZ - Deliana Permatasari; Triyono Arief Wahyudi (STREAMING, 2023)
The purpose of this study is to analyse perceived quality, availability, price, brand image towards customer satisfaction and trust its impact on the repurchase intention of herbal medicine XYZ. The research method used is survey by spreading an online structured questionnaire. The result of this research is that repurchase intention for this product affect positively and significantly by customer trust and customer satisfaction with perceived quality, availability, price and brand image.